2016
DOI: 10.1016/j.imr.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Function of specialized regulatory proteins and signaling pathways in exercise-induced muscle mitochondrial biogenesis

Abstract: Skeletal muscle mitochondrial content and function are regulated by a number of specialized molecular pathways that remain to be fully defined. Although a number of proteins have been identified to be important for the maintenance of mitochondria in quiescent muscle, the requirement for these appears to decrease with the activation of multiple overlapping signaling events that are triggered by exercise. This makes exercise a valuable therapeutic tool for the treatment of mitochondrially based metabolic disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 124 publications
(204 reference statements)
0
30
0
1
Order By: Relevance
“…PGC‐1β, another transcription factor, shares similar molecular structure and function with PGC‐1α, including nuclear receptor binding and transcriptional activation, and also regulates MB through shared mechanisms with PGC‐1α, such as activating Nrf‐1 . The nuclear respiratory factors (Nrf‐1/Nrf‐2) are associated with the expression of multiple mitochondrial proteins, such as OXPHOS complex proteins, enzymes of haeme biosynthesis and proteins involved in mitochondrial import of nuclear‐encoded subunits . Nrf‐1 transcription is regulated also by PPAR‐β in muscle of exercised rats, a mechanism that increases MB through upregulation of AMP‐activated protein kinase (AMPK) and Nrf‐1/Nrf‐2 that integrate their effects on the nuclear genes of MB with promotion of the replication and transcription of TFAM.…”
Section: Mitochondria Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…PGC‐1β, another transcription factor, shares similar molecular structure and function with PGC‐1α, including nuclear receptor binding and transcriptional activation, and also regulates MB through shared mechanisms with PGC‐1α, such as activating Nrf‐1 . The nuclear respiratory factors (Nrf‐1/Nrf‐2) are associated with the expression of multiple mitochondrial proteins, such as OXPHOS complex proteins, enzymes of haeme biosynthesis and proteins involved in mitochondrial import of nuclear‐encoded subunits . Nrf‐1 transcription is regulated also by PPAR‐β in muscle of exercised rats, a mechanism that increases MB through upregulation of AMP‐activated protein kinase (AMPK) and Nrf‐1/Nrf‐2 that integrate their effects on the nuclear genes of MB with promotion of the replication and transcription of TFAM.…”
Section: Mitochondria Physiologymentioning
confidence: 99%
“…2 The nuclear respiratory factors (Nrf-1/ Nrf-2) are associated with the expression of multiple mitochondrial proteins, such as OXPHOS complex proteins, enzymes of haeme biosynthesis and proteins involved in mitochondrial import of nuclear-encoded subunits. 19,20 Nrf-1 transcription is regulated also by PPAR-β in muscle of exercised rats, a mechanism that increases MB through upregulation of AMP-activated protein kinase (AMPK) and Nrf-1/Nrf-2 that integrate their effects on the nuclear genes of MB with promotion of the replication and transcription of TFAM. The latter is a multifunctional protein that belongs to the high-mobility group (HMG) proteins that are characterized by their ability to bend, wrap and unwind mtDNA without sequence specificity, but with preferential interaction with some identified regions.…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…To prevent age-related decline in skeletal muscle, some studies have focused on targeting the mitochondria. It is widely suggested that exercise training may reduce mitochondrial ROS because exercise can increase the antioxidant capacity in muscles 26, 27…”
Section: Age-related Changes In the Mitochondria In Skeletal Musclementioning
confidence: 99%
“…Besides stimulating the DNA binding of nuclear factors, PGC-1α activates mitochondrial transcription factor A (TFAM), which is essential for gene expression from mtDNA [31]. During exercise, PGC-1α can be activated by AMP-activated protein kinase (AMPK), silent mating type information regulation 2 homolog 1 (SIRT1), Ca 2+ /calmodulin-dependent protein kinase IV, calcineurin A, and ROS [32,33]. But PGC-1α is not just activated by ROS, it can control the level of ROS partly through the activation of nuclear factor (erythroid-derived 2)-like 2 that binds to antioxidant response element (ARE) [34].…”
Section: Mitochondrial Dynamics In Exercise and Agingmentioning
confidence: 99%